Aedes albopictus in a recently invaded area in Spain: effects of trap type, locality, and season on mosquito captures - Garrido Escudero, Mario; Veiga Neto, Jesús; Garrigós, Marta; Morales Yuste, Manuel; Recuero-Gil, Jesús; Martínez de la Puente, Josué (Scientific Reports, 2024)
Mosquitoes are primary vectors of pathogens impacting humans, wildlife, and livestock. Among them, the Asian tiger mosquito, Aedes albopictus, stands out as an invasive species with a global distribution, having established populations on every continent except Antarctica. Recent findings incriminate Ae. albopictus in the local transmission of several pathogens causing human diseases, including dengue, chikungunya, and Zika viruses and worm parasites as Dirofilaria. In Spain, the establishment of Ae. albopictus occurred in 2004 and it rapidly expanded, currently reaching southern provinces and creating novel epidemiological scenarios in recently invaded areas. In this study, we conducted captures of Ae. albopictus from May to November 2022 in two provinces, Granada and Malaga, situated near the current edge of the species' expanding range in Spain. The objective was to identify the primary factors influencing their captures in these regions. Mosquitoes were captured using BG-Sentinel traps baited with CO2 and BG-Lure, and miniature CDC-UV traps in five different localities. Our findings underscore the influence of both extrinsic factors, such as locality, and intrinsic factors, including mosquito sex, on the abundance of captured Ae. albopictus. A higher abundance of Ae. albopictus was observed in the Malaga province compared to localities in the Granada province. Furthermore, similar numbers of Ae. albopictus mosquitoes were captured in more urbanized areas of Granada, while the lowest counts were recorded in the less urbanized area. These results were compared to captures of another common species in the area, specifically Culex pipiens. Overall, these results represent the first monitoring of invasive Ae. albopictus in the area and are discussed in the light of the potential importance of the species as a nuisance for humans and vectors of pathogens of public health relevance. This study was financed by the PID2020-118205GB-I00 grant to JMP funded by MCIN/AEI/https://doi.org/10.13039/501100011033. ...